Adoption in the Digital Age Opportunities and Challenges for the 21st Century - Samuels, Julie (Springer International Publishing, 2018)
Adoption in the Digital Age explores the transformation of adoption due to social and digital media technologies. The most prolific of these changes can be seen within contact arrangements, particularly those that are not managed by an intermediary, between adopted minors and their biological kin. Within this shift, it becomes clear that this often-breached contact arrangement lends itself towards discussions about further openness within adoption. At the same time these technologies continue to document the way adopted individuals and their biological kin feel about themselves and each other. It is for these reasons that the Internet remains both a promise and threat. Samuels explores this in detail, highlighting that what it means to be adopted continues to evolve in the context of networked media cultures. Combining both theoretical discussions with the human experience of adoption, Adoption in the Digital Age will be of interest to students and scholars across a range of disciplines, including sociology, social work and cultural studies, as well as practitioners working with adoptive families and other members of the adoption triad connected and disconnected by adoption.